Liquid Waste Management at the Environmental Health Installation at Dumai Regional Public Hospital - Al Furqan; Oktavia Dewi; Herman M Purwaonegoro (Viva Medika, 2024)
The management of hospital liquid waste should be a concern based on WHO data indicating that 75% - 90% of the waste generated is household waste and 10% - 25% is hazardous waste, thus requiring management in accordance with applicable regulations. The aim of this research is to investigate the management of liquid waste carried out at the Environmental Health Installation of Dumai Regional Public Hospital in 2023. The research method used a qualitative descriptive design. Research informants were obtained using purposive sampling technique involving 6 individuals consisting of liquid waste management implementers, head of departments, and installation heads, as well as parties involved in liquid waste supervision. Data collection was conducted through in-depth interviews, document analysis, and field observations. Findings indicate the need to enhance the competency of Environmental Health Installation personnel in managing liquid waste. The management of liquid waste is expected to comply with the Standard Quality Control of Liquid Waste Management. Periodic monitoring of the physical, chemical, and microbiological quality of liquid waste is necessary. In conclusion, the management of liquid waste at the Environmental Health Installation of Dumai Regional Public Hospital in 2023 has been well conducted. This residency report demonstrates that the procedures for collection, storage, handling, and disposal of liquid waste at the hospital are in accordance with prevailing safety, environmental, and health standards.